Molecular Changes in the Cardiac RyR2 With Catecholaminergic Polymorphic Ventricular Tachycardia (CPVT) - Dulhunty, Angela F. (Frontiers in Physiology, 2022)
The cardiac ryanodine receptor Ca2+ release channel (RyR2) is inserted into the membrane of the intracellular sarcoplasmic reticulum (SR) Ca2+ store where it releases the Ca2+ that is essential for myocyte contraction. Mutations in proteins involved in excitation-contraction (EC) coupling can result in malignant changes in Ca2+ signaling, which lead to catecholaminergic polymorphic ventricular tachycardia (CPVT). The most common cellular phenotype in CPVT is a higher than normal cytoplasmic Ca2+ concentration during diastole due to excess Ca2+ leaking from the SR through mutant RyR2. Arrhythmias are triggered when the surface membrane sodium calcium exchanger (NCX) attempts to lower cytoplasmic Ca2+ by importing 3 Na+ ions in order to extrude a single Ca2+ ion. The net Na+ influx leads to delayed after depolarizations (DADs) which can trigger arrhythmia when reaching action potential threshold. Present therapies use drugs developed for other purposes that also reduce RyR2 Ca2+ leak. Such drugs can also impact on the systolic Ca2+ transient and on other target proteins. More specific drugs may prevent the effect of the mutation without changing channel regulation by endogenous factors required for normal function. Specific drugs will depend on the location of the CPVT mutation in the 4967-residue monomer. The precise way that each mutation alters the local structure and how this influences other structures along the conformational pathway leading to the pore requires structural information obtained with atomic resolution and this is only now becoming available. Gene therapy provides an alternative mutation specific technique with preliminary tests successful in animal models.